Drivers and performance outcomes of effective use of business intelligence (BI) system for managing customer relationships : A multiple case study in business-to-business sector - Fashanu, Olaitan (My University, 2021)
The era of big data has heralded and ushered in a new way of doing business and new waves of business activities. The increasing amount of data has called for new ways of managing customer relationships according to customer needs and preferences in order to increase customer value and satisfaction. These days, customers are better positioned to make in-formed decisions due to the huge amount of information readily available on the internet and other platforms. Staying ahead of the competition requires taking proactive actions and making strategic and well-informed decisions through insights gained from customer data. This can be facilitated through use of business intelligence (BI) system. While the impact of the use of BI system on firm performance has received relatively little attention, the factors that drive the effective use of BI system for managing customer relationship have received no attention. This is a first of its kind study to investigate the drivers of the effective use of BI system at two levels. Drawing on the theory of effective use and the business process per-formance framework, this study develops a theoretical framework on the determinants and performance outcomes of the effective use of BI system for managing customer relation-ships. Data was collected from 4 different companies (2 MNEs and 2 SMEs) using a multiple case study methodology. The findings reveal that organizational level determinants such as top management support and commitment, well defined goals and vision, organizational culture, BI capabilities and training drive the effective use of BI system in managing customer relationships. At the user level, the findings reveal that employee commitment, soft skills, self-efficacy drive the effective use of BI system for managing customer relationships. Fur-ther, effectively using the BI system leads to increased sales, enhanced product innovation, reduced cost, improved customer relationship, increased learning, and improved decision making. This study contributes to the understanding of how businesses can effectively use the BI system to improve business process performance in order to attain their business goals.
Keywords: big data; customer relationship management; data systems; customers; enterprises; customer satisfaction; business; business intelligence; small and medium-sized enterprises; leadership (activity); employees; data; technology; business processes; schools of economics and business administration; kansainväliset yritykset; enterprises; information and communications technology; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business